The Effect of Child Abuse by Parents on Mind Reading Ability of Children - Gholam Hossein Javanmard, Arezou Sheykhzadeh (Universitas Ahmad Dahlan, 2014)
AbstractÂ The aim of the present study was to examine the relationship between parental abuse and mind reading ability in female students. 268 female high school students were selected among high schools of Bonab city as the sample of the study by multistage cluster sampling method. The tools of the study were Reading the Mind in the Eyes Test (RMET) and two-dimensional child abuse questionnaire (Javanmard & Mamagani). In order to analyze the collected data, Pearsonâs correlation coefficient and standard multiple regression analysis were used. According to the results of the study, there was significant negative relationship between the mind reading ability of children with emotional abuse (r=-0/215, P<0/001) and physical abuse by parents (r=-0/22, P<0/001). The mentioned ability changes were predicted by emotional and physical abuse by parents.Keywords: Mind Reading Ability, Child Abuse, Parents, Children